2017
DOI: 10.1111/cod.12770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of allergens and irritants on levels of natural moisturizing factor and corneocyte morphology

Abstract: SummaryBackgroundThe irritant sodium lauryl sulfate (SLS) is known to cause a decrease in the stratum corneum level of natural moisturizing factor (NMF), which in itself is associated with changes in corneocyte surface topography.ObjectiveTo explore this phenomenon in allergic contact dermatitis.MethodsPatch testing was performed on patients with previously positive patch test reactions to potassium dichromate (Cr), nickel sulfate (Ni), methylchloroisothiazolinone (MCI)/methylisothiazolinone (MI), or p‐phenyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 37 publications
1
45
0
Order By: Relevance
“…Interestingly, Kohli and Nedorost found that AD predisposes to sensitization only to less potent allergens arguing that potent sensitizers are often strong irritants that damage the skin barrier and trigger innate immune response needed for the induction of allergic response. Consistently, Koppes et al reported that a strong contact allergen methyl⁄chloromethylisothiazolinone known for its corrosive and irritant properties causes remarkable alterations of the corneocyte surface topography and reduction in NMF, similarly to SLS. This effect was, however, not seen for nickel, a less irritant contact allergen.…”
Section: Impaired Skin Barrier As a Risk Factor For Contact Dermatitismentioning
confidence: 72%
See 1 more Smart Citation
“…Interestingly, Kohli and Nedorost found that AD predisposes to sensitization only to less potent allergens arguing that potent sensitizers are often strong irritants that damage the skin barrier and trigger innate immune response needed for the induction of allergic response. Consistently, Koppes et al reported that a strong contact allergen methyl⁄chloromethylisothiazolinone known for its corrosive and irritant properties causes remarkable alterations of the corneocyte surface topography and reduction in NMF, similarly to SLS. This effect was, however, not seen for nickel, a less irritant contact allergen.…”
Section: Impaired Skin Barrier As a Risk Factor For Contact Dermatitismentioning
confidence: 72%
“…As an alkaline detergent, SLS increases the pH of the SC affecting the activity of serine proteases (especially KLK5 and KLK7), which are known effectors of desquamation and lipid synthesis . Next, SLS dramatically decreased NMF, and this decrease was correlated with a decrease in SC hydration and changes in corneocyte surface topography . Of note, NMF is not only important for skin hydration, but also for the conformation of the keratin fibres within the corneocytes, pH of the SC and the SC levels of IL‐1 cytokines .…”
Section: The Effects Of Skin Irritants and Allergens On The Skin Barriermentioning
confidence: 99%
“…The pathomechanism of ICD remains incompletely understood; however, impairment of the skin barrier function plays a central role, triggering homeostatic and innate immune responses . Recently, Koppes et al reported 2 novel biomarkers of irritant skin reactions to sodium lauryl sulfate (SLS): the dermal texture index (DTI) as a measure of the corneocyte topography, and the levels of natural moisturizing factors (NMFs). As shown by the use of atomic force microscopy (AFM), SLS dramatically increased the number of circular nano‐objects protruding above the corneocyte surface, as shown by the DTI, and decreased NMF levels at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Koppes et al reported 2 novel biomarkers of irritant skin reactions to sodium lauryl sulfate (SLS): the dermal texture index (DTI) as a measure of the corneocyte topography, and the levels of natural moisturizing factors (NMFs). As shown by the use of atomic force microscopy (AFM), SLS dramatically increased the number of circular nano‐objects protruding above the corneocyte surface, as shown by the DTI, and decreased NMF levels at the same time. In contrast to the SLS‐induced increase in the DTI, no changes in the DTI were observed in skin affected by allergic contact dermatitis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation